Are leaf, stem and hydraulic traits good predictors of individual tree growth? (FUN2FUN project) - Martinez-Vilalta, Jordi; Rosas, Teresa; Mencuccini, Maurizio; Batlles, Carles; Regalado, Íngrid; Saura-Mas, Sandra; Sterck, Frank (Dryad, 2020)
A major foundation of trait-based ecology is that traits have an impact on
individual performance. However, trait-growth relationships have not been
extensively tested in trees, especially outside tropical ecosystems. In
addition, measuring traits directly related to physiological processes
(‘hard traits’) remains difficult and the differences between inter- and
intraspecific relationships are seldom explored. Here, we use
individual-level data on a set of hydraulic, leaf and stem traits to
explore which traits are the best predictors of basal area increment (BAI)
and growth efficiency (BAI per unit of tree leaf area, GE) among and
within species for six dominant tree species along a water availability
gradient under Mediterranean climate (Catalonia, NE Spain). Measured
traits include: leaf mass per area (LMA), leaf nitrogen concentration (N),
leaf C isotopic composition (d13C), stem wood density (WD), branch-level
estimates of the Huber value (Hv), the sapwood-specific hydraulic
conductivity (KS), the leaf-specific hydraulic conductivity (KL) and
resistance to xylem embolism (P50), and the leaf water potential at turgor
loss (Ptlp). Traits were better predictors of GE than BAI and significant
relationships were largely driven by differences among species means.
Contrary to our initial hypotheses, high values of both growth metrics
were associated with ‘conservative’ leaf and hydraulic traits. In
particular, BAI was negatively associated with wood density and hydraulic
efficiency per unit leaf area (KL), while GE increased with LMA,
allocation to sapwood relative to leaves (Hv) and resistance to xylem
embolism (P50). Climate effects on BAI and GE were indirectly mediated by
changes in traits, stand structure and tree size. Overall, these results
suggest that maintaining functionality over extended periods of time may
be more important that maximum gas exchange or hydraulic capacity to
achieve high radial growth under Mediterranean climates. Our study reveals
that the relationships between ‘functional’ traits and tree performance
along environmental gradients are complex and do not necessarily conform
to simple hypotheses based on our understanding of organ-level processes.
Trait integration along common axes of variation together with a
revaluation of the variables that better reflect whole-tree performance
can greatly improve our understanding of trait-growth relationships.
Keywords: FOS: Natural sciences